Enhanced microglial pro‐inflammatory response to lipopolysaccharide correlates with brain infiltration and blood–brain barrier dysregulation in a mouse model of telomere shortening. Issue 6 (3rd August 2015) - Raj, Divya D. A.; Moser, Jill; van der Pol, Susanne M. A.; van Os, Ronald P.; Holtman, Inge R.; Brouwer, Nieske; Oeseburg, Hisko; Schaafsma, Wandert; Wesseling, Evelyn M.; den Dunnen, Wilfred; Biber, Knut P. H.; de Vries, Helga E.; et al.
Summary: Microglia are a proliferative population of resident brain macrophages that under physiological conditions self‐renew independent of hematopoiesis. Microglia are innate immune cells actively surveying the brain and are the earliest responders to injury. During aging, microglia elicit an enhanced innate immune response also referred to as 'priming'. To date, it remains unknown whether telomere shortening affects the proliferative capacity and induces priming of microglia. We addressed this issue using early (first‐generation G1 mTerc −/− )‐ and late‐generation (third‐generation G3 and G4 mTerc −/− ) telomerase‐deficient mice, which carry a homozygous deletion for the telomerase RNA component gene ( mTerc ). Late‐generation mTerc −/− microglia show telomere shortening and decreased proliferation efficiency. Under physiological conditions, gene expression and functionality of G3 mTerc −/− microglia are comparable with microglia derived from G1 mTerc −/− mice despite changes in morphology. However, after intraperitoneal injection of bacterial lipopolysaccharide (LPS), G3 mTerc −/− microglia mice show an enhanced pro‐inflammatory response. Nevertheless, this enhanced inflammatory response was not accompanied by an increased expression of genes known to be associated with age‐associated microglia priming. The increased inflammatory response in microglia correlates closely with increased peripheral inflammation, a loss of blood–brain barrier integrity, and infiltration of immune cells in the brain parenchyma in this mouse model of telomere shortening.